Modal Sosial Komunitas Bujang Squad dalam Pengembangan Wisata Tahura Gunung Mangkol di Desa Terak Kabupaten Bangka Tengah - Dea Tamara; Kiki Fitriani; Abdul Rohim; Laila Hayati; Putra Pratama Saputra (Ideas Publishing, 2023)
Tourism development with social capital assistance can have a positive impact on communities because it contains norms, actions, and values for managing social capital that can motivate community participation in tourism development. The research was intended to describe social capital for the Bujang Squad in efforts to develop tourist villages in Terak village, Central Bangka. The methods in this study use descriptive qualitative methods. According to the study, the social capital in the Terak village was formed into three sections of trust, norms, and social networks.